(3GdaUhds - (3eMeO Hf eMehO Hf MSjf, eLO GdOjf GdoCrSoQhnTfj,J (B632 (3g` s ((3eMeO GdaNQi s)
(3ChdgG (B:s
(3GdaUd GdMGOi hGdYTQhf ef aUhd GdGSJQTfi ai eSGFd fHY GdhaGA hCMcGeg hTQGFWg s
(3BNQgG (B:s
(3aEf Gddg JYGdi jbhd hbhdg GdMb hahb cd Pi Yde Ydje s
(3HChdg agQSJ ddeNWhWs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B86 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B317s
Keywords: (3Gdabg GdMfajs